Five‐year efficacy and safety of tildrakizumab in patients with moderate‐to‐severe psoriasis who respond at week 28: pooled analyses of two randomized phase III clinical trials (reSURFACE 1 and reSURFACE 2). (4th May 2021) - Thaci, D.; Piaserico, S.; Warren, R.B.; Gupta, A.K.; Cantrell, W.; Draelos, Z.; Foley, P.; Igarashi, A.; Langley, R.G.; Asahina, A.; Young, M.; Falqués, M.; et al.
Summary: Background: The phase III reSURFACE 1 and reSURFACE 2 (NCT01722331/NCT01729754) trials of the anti‐interleukin‐23p19 monoclonal antibody tildrakizumab (TIL) for psoriasis treatment are complete. Objectives: We present 5‐year pooled data from reSURFACE 1 and reSURFACE 2. Methods: reSURFACE 1 and reSURFACE 2 were double‐blind, randomized, controlled studies with optional long‐term extensions. Adults with moderate‐to‐severe chronic plaque psoriasis were randomized 2 : 2 : 1 to TIL 100 mg (TIL 100) or 200 mg (TIL 200) or placebo at weeks 0 and 4, and every 12 weeks thereafter [reSURFACE 2 included an etanercept (ETN) arm]. Efficacy outcomes included proportions of patients achieving absolute and relative improvement from baseline Psoriasis Area and Severity Index (PASI) score through week 244 in TIL responders (≥ 75% improvement from baseline PASI; PASI 75 response) continuously receiving the same dose and ETN partial responders and nonresponders (PASI < 75 response) switched to TIL 200 at week 28. Safety was assessed from adverse events (AEs) in all patients as treated. Results: Efficacy analyses included 329 and 227 week 28 responders to TIL 100 and TIL 200, respectively, and 121 ETN partial responders/nonresponders switched to TIL 200 at week 28. Of TIL 100 or TIL 200 responders and ETN partial responders/nonresponders entering the extensions, 235/302, 176/213 and 85/107, respectively, were evaluated at week 244, and 88·7%, 92·5% and 81·3%, respectively, achieved PASI 75 response. Exposure‐adjusted rates of serious AEs were 6·3 and 6·0 patients with events per 100 patient‐years of TIL 100 and TIL 200, respectively. Conclusions: TIL treatment provided sustained disease control over 5 years in week 28 TIL responders and ETN partial responders/nonresponders, with a reassuring safety profile. Abstract : What's already known about this topic? Tildrakizumab (TIL) is approved for treatment of moderate‐to‐severe psoriasis, and 3‐year data have been previously published. Long‐term efficacy and safety data of biological therapies is crucial to inform clinical practice. What does this study add? TIL is the first anti‐interleukin‐23p19 treatment for which 5‐year efficacy and safety data are reported from two phase III studies, reSURFACE 1 and reSURFACE 2. These data provide evidence of sustained efficacy in TIL responders and in patients switched from etanercept to TIL at week 28, and a favourable long‐term safety profile with total TIL exposure of over 5400 patient‐years. Linked Comment: C.G. Purvis et al. Br J Dermatol 2021; 185 :242–243 . Plain language summary available online